Computational power of weighted splicing systems - Gan, Yee Siang; Turaev, Sherzod; Fong, Wan Heng; Sarmin, Nor Haniza (Bulgarian Academy of Sciences, 2014)
A weighted splicing system is a restriction of splicing systems in which weights are associated with the axioms, and the weight of a string z generated from two strings x and y is computed from the weights of x and y according to some operations defined on the weights. In this paper we study the computational power of weighted splicing systems considering different weighting spaces and cut-points. We also investigate the relationships of different variants of weighted splicing systems.